Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So I have $f(x)=e^x-1-x$, MVT gives me $f'(c)={f(x)-f(0)\over{x-0}}={e^x-x-1\over x}$. So $f(x)=xf'(c)$. I got stuck at how exactly I can explain that $f(x)\ge 0\, \forall\, x\ge0$

I know that $f'(c)$ has the same sign as $c$ which has the same sign as $x$, thats why $f'(c)\ge0$ when $x\ge0$, which makes $f(x)\ge0$, but how do I show it nicely?

share|improve this question

1 Answer 1

up vote 3 down vote accepted

You know that for any $x\geqslant 0$ there exists $\xi\in[0,x]$ such that $\frac{f(x)-f(0}{x-0}=f'(\xi)$, or this all says that $\frac{e^x-1-x}{x}=f'(\xi)=e^\xi-1\geqslant 0$ (since $e^x-1$ is nonnegative on the non-negative reals) and so $e^x-1-x\geqslant 0$.

share|improve this answer
    
How did you get from ${e^x}-1-x\over x$ to $e^\xi -1$? –  Akaichan Dec 11 '12 at 4:39
    
Oh, never mind, I know why. Sorry! –  Akaichan Dec 11 '12 at 4:41

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.